Kajian Pengembangan Wisata Religi Di Kabupaten Banjar Kalimantan Selatan - Muhammad Arief Anwar (Jurnal Kebijakan Pembangunan, 2019)
One of South Kalimantan's development priorities is to realize South Kalimantan as one of the national tourism destinations. One type of tourism that is now developing is religious tourism. Banjar Regency, with its capital city of Martapura is well-known as "Santri City and the Porch of Mecca", while the citizen were known to have religious potential for developing religious tourism. In Banjar Regency, there are many graves of old religious scholars and mosques that have tremendous historical value. The graves of historical scholars and mosques are crowded with tourists who not only come from the Kalimantan region but also come from various area such as Java, Sumatra, Madura, Maluku and even from abroad. In an effort to develop the potential of existing religious tourism, it is deemed necessary to conduct a study related to the development of religious tourism in Banjar Regency. The purpose of this study is; (1) Analysing the distribution of religious based tourism objects that can be developed as religious tourism objects; (2) Analysing the problems and obstacles faced in relation to the development of existing religious tourism based on; (3) Establish policy recommendations / strategies that need to be taken in the development of religious tourism in the Banjar District. The analytical method used is descriptive qualitative analysis, use to describe the development of religious tourism. This research concludes that in general there are 27 religious tourism area in Banjar Regency, and the constraints that exist in religious tourism objects are related to facilities and infrastructure, weak local resources to support tourism objects, and weak tourism marketing. To overcome the obstacles, the strategy that can be done is related to the development of tourism facilities and infrastructure development, local resource development, and marketing development. Abstrak Salah satu prioritas pembangunan Provinsi Kalimantan Selatan (Kalsel) adalah mewujudkan Kalsel sebagai salah satu destinasi wisata nasional. Salah satu jenis wisata yang sekarang berkembang adalah wisata religi. Kabupaten Banjar dengan ibukotanya Martapura dikenal dengan predikat “Kota Santri dan Serambi Mekkah”. Di Kabupaten Banjar banyak terdapat makam-makam para ulama dan masjid tua yang memiliki nilai sejarah. Makam-makam ulama dan masjid bersejarah tersebut ramai dikunjungi para wisatawan/peziarah yang bukan saja berasal dari wilayah Kalimantan tetapi juga datang dari berbagai daerah dari Pulau Jawa, Sumatera, Madura, Maluku, serta dari luar negeri. Dalam upaya mengembangkan potensi wisata religi yang ada, maka dipandang perlu melakukan suatu kajian terkait pengembangan wisata religi di Kabupaten Banjar. Tujuan dari kajian ini adalah: (1) Menganalisis sebaran objek wisata berbasis religi yang dapat dikembangkan sebagai objek wisata religi; (2) Menganalisis permasalahan dan kendala yang dihadapi terkait pengembangan wisata religi yang telah ada berdasarkan; (3) Menetapkan rekomendasi/strategi kebijakan yang perlu diambil dalam pengembangan wisata religi yang ada di Kabupaten Banjar. Penelitian ini berjenis kualitatif deskriptif dengan teknik pengambilan data melalui wawancara mendalam dengan informan yang telah dipilih berdasarkan kompetensinya terhadap pengetahuan lokasi religi di Kab. Banjar. Hasil penelitian menunjukkan ada 27 wisata religi di Kabupaten Banjar. Kendala yang dihadapi adalah berkaitan dengan sarana dan prasarana, lemahnya daya dukung sumber daya lokal terhadap keberadaan objek wisata, dan minimnya pemasaran pariwisata bertema religi. Untuk mengatasi kendala tersebut maka strategi yang dapat dilakukan adalah pengembangan sarana dan prasarana wisata, pengembangan sumber daya lokal, dan pengembangan pemasaran.